Coming out of isolation: impacts of COVID-19 on physical activity, diet, mental well-being, and sleep over time - Joel Billings; Allison Kwesell; Stephanie Cosby; Shuyang Lin (Frontiers in Psychology)
IntroductionThe COVID-19 pandemic lockdown significantly disrupted daily routines and impacted physical activity, diet, mental well-being, and sleep. This mixed-methods study investigates these changes over three periods—pre-pandemic, pandemic onset, and one-year post-onset—to understand their causes and inform public health policy for improved resilience during future crises.MethodsA mixed-methods study was conducted with 34 US participants who completed open-ended qualitative questions and quantitative assessments in May 2020 and May 2021. Participants were recruited via social media from 10 states with high COVID-19 cases. Quantitative data categorized health changes (positive, negative, or no change), while qualitative data were analyzed thematically to explore reasons for these changes and uncover interrelationships among health behaviors.ResultsQuantitative results showed that, during the pandemic onset, most participants experienced negative changes in diet, mental well-being, and sleep, while physical activity varied. By one-year post-onset, improvements were noted across all health pillars, with mental well-being and sleep showing the most significant positive changes. Thematic analysis of qualitative data revealed stress, anxiety, and personal motivations as key drivers of health behaviors. Participants’ narratives provided a deeper understanding of these shifts that a Likert-style survey alone could not capture, highlighting the interconnectedness of health pillars.DiscussionThe findings demonstrate the importance of addressing mental well-being to improve overall health resilience. Public health interventions should prioritize mental health and consider the interrelated nature of health behaviors. The mixed-methods approach combined quantitative trends with qualitative insights, offering a comprehensive understanding of why health changes occurred, providing actionable guidance for future public health policy.